Sexual dysfunction in patients after double‐J catheterisation: A cross‐sectional, prospective study. Issue 10 (4th July 2021) - Özlü, İbrahim; Karaman Özlü, Zeynep; Kilinç, Tülay; Yayla, Ayşegül; Karabulut, İbrahim
Abstract: Objective: This study was conducted to examine sexual dysfunction in patients after double‐J catheterisation. Materials and Methods: This descriptive, cross‐sectional and prospective study was conducted in a research and training hospital from June 2020 to February 2021. The data were collected from patients who visited the emergency clinic and were hospitalised in the urology clinic because of renal calculi. The study was completed with 192 patients. The data were collected using a patient introductory form, the International Index of Erectile Function (IIEF‐15) and the 5‐item Turkish version of the International Index of Erectile Function (IIEF‐5). Then data were collected before double‐J catheterisation, 1 month after catheterisation and a month after the catheter was removed. The data were evaluated using means, numbers, percentile distributions and the paired samples t test. Results: The patients' sexual function was negatively affected by double‐J catheterisation, and this negative effect persisted for a month after removal of the double‐J catheter. The differences in the patients' mean IIEF scores and sub‐dimension scores before and after double‐J catheterisation were statistically significant ( P  ˂ 0.001). A month after the double‐J catheter was removed, the difference between their mean IIEF‐5 scores was statistically significant ( P  ˂ 0.001). No erectile dysfunction was found in 50.0% of the patients before double‐J catheterisation. A month after the catheter was removed, erectile dysfunction was found at different levels in 88% of the patients, and severe erectile dysfunction was found in 60.9% of the patients. Conclusion: This study found that double‐J catheterisation negatively affects patients' sexual function. Patients experience sexual dysfunction while the double‐J catheter is in place and for a month after it is removed.